Marine Bromopyrrole Alkaloids: Synthesis and Diverse Medicinal Applications - Rane, Rajesh; Sahu, Niteshkumar; Shah, Chetan; Karpoormath, Rajshekhar (Current Topics in Medicinal Chemistry, 2014)
Marine organisms have been found to be a very rich source of bioactive molecules. Among marine organisms, sponges have been proven to be excellent producers of secondary metabolites. More than 5,300 compounds have been isolated from sponges with around 200 new molecules reported each year. Bromopyrrole alkaloids constitute a family of exclusively marine alkaloids and represent a fascinating example of the large variety of compounds formed by marine sponges which exhibit different biological activities such as antifeedent, anti-biofilm, anticancer, antiinflammatory, antimicrobial, immunomodulatory, analgesic, antiserotonergic, antiangiogenic, antihistaminic, chitinase inhibitor and actimyosin ATPase activator. More than 140 derivatives with different structures and biological activities, have been isolated from more than 20 different sponges. Most of these alkaloids share a key building block, pyrrole-imidazole with oroidin being their underlying structural motif. In this review detailed account of isolation and medicinal application of marine bromopyrrole alkaloids and their synthetic derivatives are discussed.
Keywords: antibiofilm agents